Understanding the Spirit of Great Physician from inheritance of Traditional Chinese Medicine nursing (从中医护理传承领悟大医精诚) - FAN Yanmei (樊艳美) (中西医结合护理, 2023)
Sun Simiao's "Spirit of Great Physician" is an exemplary work to discuss the thought of medical ethics in ancient China. From the point of view of a disciple of nursing inheritance of Traditional Chinese Medicine, this paper discussed from the four aspects of "proficiency in medical skills", "sincerely saving people", "the behavior of a medical workers " and "the standardized of treatment". This paper expounds the medical moral cultivation of "great doctor" in Sun Simiao's "Spirit of Great Physician" and how to become a " Great medical workers " combined with teacher Shu Yuling and the author's own clinical experience. " Spirit of Great Physician " medical ethics, as the value guidance of medical workers, leading medical workers to make concerted efforts to overcome the epidemic, will continue to be inherited and carried forward in the construction of the new era. (《大医精诚》是我国古代论述医德思想的典范之作。本文从“医术精通”“诚心救人”“大医之体”“为医之法”四个方面对《大医精诚》中“大医”应具备的医德修养以及怎么才能成为“大医”, 并结合舒玉苓老师及笔者自身临床实践进行了阐述, 旨在将“大医精诚”之医德继续传承与发扬。)